The Effect of Ethanolic Extract for Cyperus rotundus Rhizomes on Liver in Male Albino Mice (Baghdad Science Journal, 2015)
The present study designed to determine the ethanolic extract of Cyperus rotundus on Liver in Albino Male Mice . In the present study 18 Male mice were used they divided into six groups ( 1st group consedered control group , 2nd group injected by 250 mg/ml from extract , 3th group injected by 300 mg/ml from extract , 4th group injected by 350 mg/ml from extract , 5th group injected by 400 mg/ml from extract and the 6th group injected by 450 mg/ml from extract ) . the expermint lasted for two days and the doses gived by intraperitonial injection . showed from the study results that ethanolic extract for Cyperus rotundus have negative effect on Liver tissue in 250 , 300 , 350 mg/ml concentrations when comparsion with control group . the results from two last groups was the same effect to the first three groups but was more negative on Liver tissue from the first three groups treated . We concluded from the present results that ethanolic extract from rhizomes of Cyperus rotundus have negative effect on liver tissue in the different concentrations .